Étude de relance auprès des détenus fédéraux traités en milieu psychiatrique : description des antécédents, du séjour, des rechutes et des récidives - Hodgins, Sheilagh; Cyr, Mireille; Paquet, Jean; Lamy, Pierre (Criminologie, 1988)
While severe mental disorders have consistently been shown to be more prevalent among inmates of penal institutions than among the general population, the provision of mental health within jails, prisons and penitentiaries has always been, and continues to be, problematic. The present investigation was designed to examine the impact on patients of one organizational model of mental health care for penitentiary inmates. Ninety-nine men who were transferred from a penitentiary to a maximum security hospital for varying periods of time were followed for three years after discharge. Relapse and criminal recidivism were documented from official files. Interviews were conducted at the end of the follow-up period in order to examine subject's level of social functionning and mental state. Specific conclusions are drawn about the way in which mental health care was provided and the benefit which accrued to the patients.